Fruit crops of Indian semi-arid regions: significance, conservation and utilization strategies—a review - Singh, A K; Yadav, Vikas; L P Yadav; Gangadhara K; Rao, V V Appa; Anil; Rane, Jagdish; Sahil, Anand (Current Horticulture, 2025)
Today, there is a significant demand for nutrient-dense fruits to enhance nutritional and metabolic health in humans. The production of commercial fruit crops is becoming increasingly reliant on inputs-dependent to cope with the losses caused from biotic and abiotic stresses. The region is characterized by severe environmental constraints, making the cultivation of traditional crops unprofitable. Currently, climatic conditions in semi-arid regions are changing, with issues like frost and low temperatures posing challenges for cultivation of many crops. Underutilized semi-arid fruits refer as high nutritional value, medicinal properties, and resilience in adverse soil and climatic conditions; have not received the desired attention.These semi-arid fruits offer numerous advantages, including ease of cultivation, hardiness, and resilience to climate changes, compared to major commercially grown crops. Technologies have been standardized for the large-scale multiplication of quality planting material of semi-arid zone fruits. Moreover, local communities are well-informed about the nutritional and medicinal properties of these crops. However, these lesser- known semi-arid fruits are an essential part of traditional foods, particularly in rural areas and among tribal communities. This review provides an overview of the technologies developed on semi-arid fruit crops that can transform semi-arid ecosystems into horticultural hubs, offering food, nutrition, and livelihood security to the residents.